Nature of solidification of nanoconfined organic liquid layers - Lang, X Y (Langmuir : the ACS journal of surfaces and colloids, 2007)
A simple model is established for solidification of a nanoconfined liquid under nonequilibrium conditions. In terms of this model, the nature of solidification is the conjunct finite size and interface effects, which is directly related to the cooling rate or the relaxation time of the undercooled liquid. The model predictions are consistent with available experimental results